2013
DOI: 10.1002/chem.201303426
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of 3‐Alkylidenephthalides from Benzoic Acids by a Rhodium‐Catalyzed ortho‐CH Acylation Process

Abstract: Supporting information for this article is available on the WWW under http://dx.doi.org/10.1002/chem.201303426. Figure 1. Examples of biologically active alkylidenephthalides. Scheme 1. Synthetic entries to alkylidenephthalides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…More importantly, the carboxyl group is able to capture the intermediates to afford oxygen heterocycle motifs . In this context, as shown in Scheme , Gooßen synthesized 3‐alkylidenephthalides (a mixture of Z ‐ and E ‐isomers) from benzoic acids or aliphatic acids and anhydrides via a one‐pot C−H acylation/elimination cascade reaction . Lee et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the carboxyl group is able to capture the intermediates to afford oxygen heterocycle motifs . In this context, as shown in Scheme , Gooßen synthesized 3‐alkylidenephthalides (a mixture of Z ‐ and E ‐isomers) from benzoic acids or aliphatic acids and anhydrides via a one‐pot C−H acylation/elimination cascade reaction . Lee et al.…”
Section: Methodsmentioning
confidence: 99%
“…[10] More importantly, the carboxyl group is able to capture the intermediates to afford oxygen heterocycle motifs. [12] Lee et al reported the palladium-catalyzed tandem CÀH olefination and oxidative coupling of ortho-substituted benzoic acids with vinylarenes to produce (Z)-3-benzylidenephthalides. [12] Lee et al reported the palladium-catalyzed tandem CÀH olefination and oxidative coupling of ortho-substituted benzoic acids with vinylarenes to produce (Z)-3-benzylidenephthalides.…”
mentioning
confidence: 99%
“…The same year, Gooßen and co‐workers synthesized 3‐alkylidenephthalides by a carboxylate‐directed olefination via a one‐pot C−H acylation/acylalization/elimination cascade (Scheme ) . Importantly, they showed that the transformation can be achieved from two carboxylic acids by using pivalic anhydride as an activating agent.…”
Section: C−c Bond Formationmentioning
confidence: 99%
“…[1] During the preparation of the review, the Gooßen group reported the ortho-acylation of benzoic acids to form o-acyl benzoic acids, Scheme C1, [2] and 3-alkylidenephthalides, Scheme C2. [3] The authors apologize that this work was overlooked.…”
Section: Cover Picturesmentioning
confidence: 99%